Pengelolaan Sampah Organik Melalui Budidaya Maggot - Muntaqo, Arif; Sulung, Puspita; Putranti, Amalina Dwi; Rosyadi, Aulia; Avisina; Faelasufa, Isye (Profetik: Jurnal Pengabdian Masyarakat, 2023)
Garbage is a consequence of human activity. Waste generation will increase along with population growth and community consumption patterns. Processing organic waste requires appropriate technology so that the processed products do not produce waste again. Bioconversion technology using Black Soldier Fly (BSF) maggots can be used to convert organic material so that it has economic potential. Even BSF maggots are able to degrade organic waste faster than other insects. Apart from that, the products produced from processing organic waste by BSF maggots have high economic value. For example, BSF maggots can be a source of protein that can be used as an alternative feed for livestock such as catfish and chickens, and kasgot (maggot former) can be used as an alternative solution to substitute NPK fertilizer from the government. It is hoped that this outreach & training on BSF maggot cultivation will increase the knowledge and skills of training participants to solve environmental problems related to organic waste through bioconversion technology. The implementation method is carried out by lectures/socialization and training. High public enthusiasm and increasing public knowledge, especially mothers, who are the biggest producers of organic waste from their kitchens, achieved 100% in cultivating BSF maggots, which is a measure of success in this training. Thus, the people of Bersole Village have the potential to become a target village for cultivating BSF maggots.